Comparison of Complex Sadik and KAJ Transforms for Ordinary Differential Equations to the Response of an Uncompressed Forced Oscillator - Turq, Saed M.; Emad A. Kuffi (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
In this paper we have presented a comparison between two novel integral transformations that are of great importance in the solution of differential equations. These two transformations are the complex Sadik transform and the KAJ transform. An uncompressed forced oscillator, which is an important application, served as the basis for comparison. The application was solved and exact solutions were obtained. Therefore, in this paper, the exact solution was found based on two different integral transforms: the first integral transform complex Sadik and the second integral transform KAJ. And these exact solutions obtained from these two integral transforms were new methods with simple algebraic calculations and applied to different problems. The main purpose of this comparison is the exact solutions, and until we show the importance of the diversity and difference of the kernel of the integral transform by keeping the period t between 0 and infinity.